The Causal Impact of Distance on Bank Lending - Herpfer, Christoph; Mjøs, Aksel; Schmidt, Cornelius (Management Science, 2023)
We investigate the role of physical distance in corporate lending by exploiting infrastructure improvements as shocks to travel time. Lower travel time increases the likelihood of initiating a new banking relationship, consistent with an economic surplus from lower transaction costs. In existing lending relationships, banks capture part of this surplus by increasing interest rates, in particular, if banks have higher bargaining power. Reductions in travel time to competing banks have the opposite effects. Banks benefit from improved infrastructure through an increase in clients, and lenders that rely more on technology do not exhibit sensitivity to changes in distance. This paper was accepted by Victoria Ivashina, finance. Funding: Financial support from Finans|Bergen is gratefully acknowledged. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2022.4346 .